Pemberdayaan Ekonomi Berbasis Home Industry untuk Meningkatkan Kesejahteraan Ibu Rumah Tangga di Desa Karangpatihan - Mujahidin, Gusrijal; Adi Nugroho, Irfan (STAI Terpadu Yogyakarta, 2024)
Economic empowerment based on home industry is an effort to improve the welfare of housewives in Karangpatihan Village. This study aims to analyze the impact of this economic empowerment program on income, skills, and long-term changes in family economy. The method used is a Participatory Action Research (PAR) approach with the implementation of entrepreneurship training for local housewives. The results of the study indicate that the program successfully increased the income of housewives through more organized and productive home-based businesses. In addition, their skills in running independent businesses significantly improved. In the long term, this empowerment has led to better family financial management and increased female participation in economic decision-making within the household. This empowerment program has made a significant contribution to the economic resilience of families in Karangpatihan Village